Propuesta de adaptación del documento ASCE/SEI31-03 “Evaluación Sísmica De Edificaciones Existentes” (2014)
This document presents a proposal to adapt the standard ASCE / SEI31-03 "Seismic Evaluation of Existing Buildings" of the American Society of Civil Engineers, to provide an evaluation methodology of existing buildings in Colombia. This methodology contains the evaluation procedure of buildings of various structural systems with materials such as: wood, masonry, steel and reinforced concrete; it also determines and progressively analyzes, and with incremental complexity, the possible deficiencies presented by structural, non-structural elements, foundations and geological risks, through the evaluation of resistance, rigidity, structural configuration and basic details of ductility. In this way, there will be tools for choosing the rehabilitation procedure based on the improvement of the seismic performance of the building. Considering that in Colombia the existing information for evaluation and subsequent seismic rehabilitation does not provide a prescriptive orientation to evaluate the existing constructions, it is necessary to contribute to the enrichment of the elements contained in the Colombian earthquake-resistant construction regulation -NSR-10- through a proposal to adapt document ASCE / SEI31-03 "Seismic Assessment of Existing Buildings"